INTERNATIONAL EXPERIENCES ON PILGRIMAGE TOURISM AND OPPORTUNITIES TO USE THEM IN THE DEVELOPMENT OF STRATEGIES FOR INDEPENDENT TOURISM DEVELOPMENT (Marketing Journal, 2025)
This article explores international practices in pilgrimage tourism and examines how they can be adapted to Uzbekistanʼs tourism development strategy. Successful models from Morocco, Indonesia, Turkey, Malaysia, and Kazakhstan are analyzed as potential fra meworks for a national concept.
Keywords: pilgrimage tourism; Sufi heritage; international experience; infrastructure; tourism strategy; religious heritage; spiritual tourism